2017
DOI: 10.1016/j.neuro.2016.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and functional expression of intracellular loop variants of the honey bee (Apis mellifera) RDL GABA receptor

Abstract: The insect GABA receptor, RDL (resistance to dieldrin), plays central roles in neuronal signalling and is the target of several classes of insecticides. To study the GABA receptor from an important pollinator species, we cloned Rdl cDNA from the honey bee, Apis mellifera. Three Rdl variants were identified, arising from differential use of splice acceptor sites in the large intracellular loop between transmembrane regions 3 and 4. These variants were renamed from previously, as Amel_RDLvar1, Amel_RDLvar2 and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(46 citation statements)
references
References 46 publications
2
42
2
Order By: Relevance
“…All the eight full length clones for Apisum Rdl2 encoded for the exon3b variant; however, four of these clones had open reading frames of 1674 bp, whilst the other four had 1677 bp, encoding 557 and 558 amino acids, respectively. The difference in the open reading frame lengths is due to the presence of either a TVR or TEVR peptide motif in the TM3-TM4 intracellular domain, which were previously found in A. mellifera RDL, and were denoted variants 1 or 2, respectively [31]. No potential A-to-I RNA editing was observed in the twenty clones analysed.…”
Section: Resultsmentioning
confidence: 83%
See 4 more Smart Citations
“…All the eight full length clones for Apisum Rdl2 encoded for the exon3b variant; however, four of these clones had open reading frames of 1674 bp, whilst the other four had 1677 bp, encoding 557 and 558 amino acids, respectively. The difference in the open reading frame lengths is due to the presence of either a TVR or TEVR peptide motif in the TM3-TM4 intracellular domain, which were previously found in A. mellifera RDL, and were denoted variants 1 or 2, respectively [31]. No potential A-to-I RNA editing was observed in the twenty clones analysed.…”
Section: Resultsmentioning
confidence: 83%
“…In line with this, more recent studies have shown that 100 μM imidacloprid acted as an antagonist of An. gambiae and A. mellifera RDL expressed in Xenopus oocytes [12,31]. We show here that imidacloprid at 100 μM has no antagonistic actions on Apisum RDL1 or Apisum RDL2, highlighting the fact that RDL can respond to neonicotinoids in a species-dependent manner.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations